2021
DOI: 10.3390/agronomy11030407
|View full text |Cite
|
Sign up to set email alerts
|

Reducing N Fertilization without Yield Penalties in Maize with a Commercially Available Seed Dressing

Abstract: Introducing smart and sustainable tools for climate change adaptation and mitigation is a major need to support agriculture’s productivity potential. We assessed the effects of the processed gypsum seed dressing SOP® COCUS MAIZE+ (SCM), combined with a gradient of N fertilization rates (i.e. 0 %, 70 % equal to 160 kg N ha-1, and 100 % equal to 230 kg N ha-1) in maize (Zea mays L.), on: (i) grain yield, (ii) root length density (RLD) and diameter class length (DCL), (iii) biodiversity of soil bacteria and fungi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 71 publications
2
10
0
2
Order By: Relevance
“…Rosa [10] has argued that winter turnip rape (Brassicaceae) and white clover (Fabaceae) positively affected the quality of sweet maize kernels by increase of vitamin C concentration and reduction of P concentration, which was partially supported by results achieved in this experiment. Furthermore, increased kernel yield and concentration of glucose, fructose, vitamin C, Mg, Fe, and Zn in the variant with BF proves its importance as sustainable practice [12][13][14].…”
Section: Variability In Chemical Composition Of Sweet Maize Kernelmentioning
confidence: 84%
See 2 more Smart Citations
“…Rosa [10] has argued that winter turnip rape (Brassicaceae) and white clover (Fabaceae) positively affected the quality of sweet maize kernels by increase of vitamin C concentration and reduction of P concentration, which was partially supported by results achieved in this experiment. Furthermore, increased kernel yield and concentration of glucose, fructose, vitamin C, Mg, Fe, and Zn in the variant with BF proves its importance as sustainable practice [12][13][14].…”
Section: Variability In Chemical Composition Of Sweet Maize Kernelmentioning
confidence: 84%
“…Phenolics could also reduce the bio-availability of essential elements [17], so CC with reducing potential of phenolics accumulation in maize kernel, such as fodder kale (T4) and field pea + winter oats (T5) are advantageous. In general, higher values of ratio between phytic acid and essential elements were noticed in BF variant, contributing to the increased availability of essential macro-and micro-elements from poorly accessible forms [13,14,44]. It is important to emphasize that enhanced absorption of essential elements from the maize kernel during digestion could be enhanced by the increased YP concentration [18,19], what was obtained in variants without BF.…”
Section: Potential Bio-availability Of Essential Elementsmentioning
confidence: 87%
See 1 more Smart Citation
“…In the present case study, located in eastern Lombardy (Italy), maize production is experiencing relevant variability, being caused mainly by the low price on the market and pest control regulations and limits, which results in increased imports from countries outside the EU [31]. It was observed that dairy farmers hardly adhere to the organic recommended fertilizer application rates due to the high availability of manure and slurry [28,[32][33][34][35][36]; however, to ensure high crop yields, topdressing mineral N is used despite the purchase and environmental costs [37]. Even considering the current subsidized rates, mineral fertilizers still represent a substantial budget item in European farms [38].…”
Section: Introductionmentioning
confidence: 81%
“…The proximal sensing equipment is typically used to manage different field homogeneous zones, also known as management zones. They represent subfield regions with the same soil traits and hydrologic characteristics within which a single strategy (e.g., fertilization rate) is appropriate [26][27][28]. Since it is now possible to map the maize yields and moisture level at harvest with very high spatial resolution, the major challenge is modulating the amount of fertilizer equally to match the crop demand [29].…”
Section: Introductionmentioning
confidence: 99%